Perbandingan Metode Selection Sort dan Insertion Sort Dalam Pengurutan Data Menggunakan Bahasa Program Java - Endang Sunandar (PETIR, 2019)
There are various kinds of sorting data methods that we know of which are Bubble Sort, Selection Sort, Insertion Sort, Quick Sort, Shell Sort, and Heap Sort methods. All of these methods have their respective strengths and weaknesses, the use of which is determined based on needs. Each method has a different algorithm, where the difference in this algorithm affects the execution time. In this paper the authors make a comparison of the 2 methods of sorting data, namely the Sort Sort and Insertion Sort methods, with consideration that the two methods are concise algorithms and have almost the same algorithm pattern. , using the same number and data model. The purpose of this comparison is to provide an overview of the two methods, which method has faster execution time, whether the Selection sort method or the Insertion Sort method.